Implementasi Augmented Reality (AR) Berbasis Android Sebagai Pengenalan Rumah Adat Indonesia Bagian Barat - Sulistyowati, Novia; Waliyansyah, Rahmat Robi; Murti Dewanto , Febrian (JUSS (Jurnal Sains dan Sistem Informasi), 2020)
A traditional house is a house that has a unique building characteristic in an area that describes the culture of the area itself. Traditional houses are also unique in terms of form, function and meaning of the building. As Indonesians, we must introduce one of the existing cultures so that it is not forgotten by the community, especially school children. Judging from the development of technology, we must make new things in introducing traditional houses. From the results of research conducted at SD IT BINA INSANI, the teachers there still use conventional media in the form of textbooks and thematic books for the learning process. Therefore, the authors created an application to introduce western Indonesian traditional houses using Augmented Reality called RA-IBB as an introduction medium. This application is based on Android so that teachers can easily explain material about traditional houses and can show traditional houses in 3D without having to come directly to the province. And for students to be able to study traditional houses wherever and whenever. The making of this application uses the waterfall method for the development stage. The RA-IBB application contains materials about western Indonesian traditional houses and their 3d objects and quiz questions that use random shuffle algorithm questions. The random shuffle algorithm is a randomized question from an array or record. Based on the User Acceptance Test (UAT) for teachers, the results obtained from several aspects, namely the design aspect yields a percentage of 91%, the application information aspect produces a percentage of 91.